Assessing swallowing disorders in adults on high-flow nasal cannula in critical and non-critical care settings. A scoping review protocol. - Ruvistay Gutierrez-Arias; Gabriel Salgado-Maldonado; Paola Letelier Valdivia; Francisco Salinas-Barahona; Carmen Echeverría-Valdebenito; Pamela Seron; INTRehab Research Group (PLoS ONE)
Introduction The high-flow nasal cannula (HFNC) has become a widely used respiratory support system, which has proven to be effective in different populations. The facilitation of oral communication and feeding have been described as advantages of this support. Nevertheless, swallowing disorders associated with the use of HFNC have been postulated. However, such evidence is scattered in the literature, not systematically searched, and needs to be adequately summarised. This review aimed to explore the literature, to identify and map the evidence, regarding the frequency and methods of assessment of swallowing disorders in adult HFNC users, in both critical and non-critical units. Materials and methods A scoping review will be conducted. A systematic search in MEDLINE (Ovid), Embase (Ovid), CENTRAL, CINAHL (EBSCOhost), and other resources will be conducted. Primary studies, in any language or publication status, assessing the incidence of swallowing disorders in adults with HFNC support will be included. Two reviewers will independently select studies and extract data. Disagreements will be resolved by consensus or a third reviewer. The results will be reported narratively, using tables and figures to support them. Discussion Positive end-expiratory pressure generated in the airway by HFNC could impair the proper swallowing performance. Knowing the methodological characteristics, the instruments or scales used to assess the presence of dysphagia, and the results of the studies may contribute to considering swallowing assessment in this population on a routine basis, as well as to guide the conduct of new studies that may respond to less researched areas in this topic. Registration Registration number: INPLASY2022110078.